Brain-Adjusted Relational Leadership: A Social-Constructed Consciousness Approach to Leader-Follower Interaction - Psychogios, Alexandros; Dimitriadis, Nikolaos (Frontiers in Psychology, 2021)
Relationship-based approaches to leadership represent one of the most fast growing leadership fields and help us understanding better organizational leadership. Relation-based approaches emphasize the relationship and interaction between the leader and the follower. The emphasis is placed on the way that they interact and influence each other at attaining mutual goals. It is known that leaders are linked to followers and vice versa in a sense of responding to other’s needs towards the achievement of mutual goals. Leaders and followers are essential part of this social process implying that they are losing their traditional identity rooted in the formal organizational structure (manager-subordinate) and become inseparable actors of a co-constructing process of leadership. What is less known though is the way that leadership actors are linked to each other and in particular how they try to understand how to do that in the workplace. What is even less understood is the importance and role of consciousness in this relationship. Especially, since consciousness appears to be both a fundamental and a very elusive element in human relations. Therefore, this paper conceptually explores the concept of consciousness within the context of the social brain theory to argue that leadership actors need to rethink their approach to individuality and focus on mutually dependent relations with each other. This paper contributes to the field of Neuro-management by introducing the concept of Homo Relationalis. In this respect, we suggest that leadership is not just social constructed element but also social brain constructed phenomenon that requires an understanding of human brain as social organ. We further recommend a new approach of applying cognitive style analysis to capture the duality of leader/follower in the same person, following the self-illusion theory. Finally, we conclude that we need to emphasise more a social brain-adjusted relational leadership approach and we introduce two new cognitive styles that can help capture the essence of it.